Wolfhart Pannenberg's Engagement with the Natural Sciences - Polkinghorne, John C. (Zygon, 1999)
Wolfhart Pannenberg's engagement with the natural sciences is surveyed. A critique is given of his treatment of these themes: the concept of a field; contingency; the role of the future.